2020
DOI: 10.1016/j.canep.2020.101780
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and cancer risk: Findings from the UK Biobank, a large prospective cohort study

Abstract: Highlights▪ Moderate physical activity levels were associated with lower risk of oropharyngeal and lung cancers ▪ High physical activity levels were associated with lung, breast, hepatobiliary and colon cancers ▪ Sensitivity analyses showed associations with lower oesophageal and higher prostate cancer incidence ▪ Results varied by deprivation, smoking, or combined body fat and physical activity ▪ Promoting high levels of physical activity may be required for cancer prevention ABSTRACT Objectives: This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 75 publications
1
17
1
Order By: Relevance
“…Indeed, PA has been identified as being an important component of cancer survivorship [17,33] and the pandemic has resulted in a decrease in PA of PLWBC [25]. Recognising the importance of PA for prostate [34], breast [25] and other cancers [35], our research confirmed that the adapted CARE programme was an important ingredient in helping PLWBC to keep physically active during the COVID-19 restrictions. Regardless of whether attendees engaged CARE online or outdoors, sessions provided an important opportunity to secure the physical, social [1,19] and mental health benefits of PA [1,19,36,37].…”
Section: Discussionsupporting
confidence: 65%
“…Indeed, PA has been identified as being an important component of cancer survivorship [17,33] and the pandemic has resulted in a decrease in PA of PLWBC [25]. Recognising the importance of PA for prostate [34], breast [25] and other cancers [35], our research confirmed that the adapted CARE programme was an important ingredient in helping PLWBC to keep physically active during the COVID-19 restrictions. Regardless of whether attendees engaged CARE online or outdoors, sessions provided an important opportunity to secure the physical, social [1,19] and mental health benefits of PA [1,19,36,37].…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, sarcopenia (low muscle mass), a prevalent condition in obese cancer patients, may need further body composition assessments using sophisticated tools to explore the obesity paradox in cancer and the potential mechanisms that could explain it. Previous studies have demonstrated that people who engage in moderate to vigorous levels of physical activity are at a lower risk of developing several cancers including lung, breast, hepatobiliary tract, colon, and oropharyngeal cancers 13,90 . Nevertheless, for some cancers, this risk reduction may be independent of the direct effect of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, observational studies have shown that low 25hydroxyvitamin D levels, in women with early-stage breast cancer, are associated with an increased recurrence risk 100 . Since outdoor physical activity can increase 25-hydroxyvitamin D levels, this could be another mechanism linking physical activity to cancer 90 . Although there is irrefutable evidence that physical activity plays an important role in preventing many cancers, the type, intensity, duration, and frequency of physical activity that have optimal effects for cancer prevention remain unclear 95 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, attenuating secondary health problems in cancer survivors has become a major public health challenge. However, cancer incidence and recurrence can be prevented with a healthy lifestyle, including regular physical activity (PA), to some extent ( Loprinzi et al, 2012 ; Lahart et al, 2015 ; Murray et al, 2020 ). PA is a modifiable behavior that is linked to several cancers and has been shown to be effective in the primary prevention of cancer ( Moore et al, 2012 ; Hojman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%